THE SYMBIOTIC RELATIONSHIP: UNVEILING THE SCIENTIFIC AND PHILOSOPHICAL BENEFITS OF BHARATANATYAM AND YOGA - Bindu S.; Bhattacharya, Arkadev (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article presents a comprehensive comparative analysis of two profound traditional Indian practices: Yoga and Bharatanatyam. While Yoga is a spiritual and physical discipline, and Bharatanatyam is a classical artistic dance form, both share foundational philosophical and scientific roots, emphasizing profound mind-body integration, personal transformation, and holistic well-being. This study meticulously examines the multifaceted advantages each discipline offers across physical, mental, intellectual, and social dimensions, drawing upon both ancient wisdom and contemporary scientific research. Yoga, through its systematic application of controlled breathing techniques (pranayama) and meditative practices, is shown to cultivate deep relaxation, mental tranquility, and enhanced cognitive function. Conversely, Bharatanatyam fosters remarkable physical endurance, sharpens memory, and refines emotional intelligence through its intricate, repetitive movements, expressive storytelling (abhinaya), and precise rhythm. This research not only highlights their enduring cultural significance but also underscores their contemporary relevance as powerful tools for health and personal development. Ultimately, Yoga and Bharatanatyam emerge as complementary systems of embodied knowledge, offering extensive benefits for personality development, therapeutic healing, and educational enrichment.